Atlasprofilax: a new promising treatment for chronic cervicobrachialgia. A qualitative-quantitative research of a retrospective longitudinal section, with a cause-effect approach - Rezende, R.; León Higuera, J. G.; Manent, L.; Lewis, K.; Angulo, O. (Frontiers in Medical Technology, 2025)
ObjectivesTo evaluate the effectiveness of the Atlasprofilax intervention in the treatment of chronic cervicobrachialgia in a cohort of 162 patients. The assessment focused on measuring pain reduction, overall patient satisfaction, and improvements in the range of motion of the neck and the affected upper-limb.MethodsA retrospective, open-label, qualitative-quantitative longitudinal cut study was conducted in an orthopedic medical center in Brazil from June 2016 to July 2017. A total of 162 Brazilian patients with diagnosed chronic cervicobrachialgia were treated with a single session of non-invasive device-mediated treatment (Atlasprofilax method) that utilizes mechanotransductive vibropercussion on the suboccipital myofascia for approximately eight minutes. Patient conditions were established at baseline, and three follow-up assessments were conducted at 1, 6, and 9 months after treatment to evaluate the endpoints. Primary endpoints included changes in the cervical VAS pain and brachial VAS pain, while secondary endpoints included changes in the range of motion of the neck and affected upper limb, as well as patient satisfaction. A single blinded examiner conducted the evaluations at baseline and follow-up assessments, and the intervention was performed by an orthopedic doctor specializing in shoulder surgery.ResultsThe primary endpoints showed a significant reduction in pain. The mean cervical VAS pain score at baseline was 7.15 ± 2.15 [median VAS 8 (6;8)], which reduced to 1.47 ± 1.04 [median 0.5 (0/2)] at month 9 [mean reduction −5.67 ± 2.30 and median −6 (−7/−4), p < 0.0001]. Fifty percent of the patients reported no pain on the VAS at the 9-month follow-up. The mean brachial VAS pain score at baseline was 6.16 ± 2.31 [median 6 (3;8)], which reduced to 0.33 ± 1.79 [median 0 (0;2)] at month 9 [mean reduction −5.83 ± 2.35; median reduction −6 (−8/−4), p < 0.0001]. At the 9-month follow-up, 88.89% of patients reported no brachial pain on the VAS. Secondary endpoints indicated a marked improvement in the average range of motion of the neck and upper limb in all subtypes of measurements. Additionally, 87.04% of patients reported satisfaction with the therapy and an improvement in their daily activities. No side-effects were observed.ConclusionsAtlasProfilax is nowadays a good option as an intervention when it comes to pain control and activities of daily living.